Pengaruh Gaya Kepemimpinan Kepala Desa terhadap Kinerja Perangkat Desa: Studi Kuantitatif di Kabupaten Sumbawa - Pratama, Ahmad Fadli; Zahra Aulia, Nadia (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to examine the effect of village head leadership style on the performance of village officials in Sumbawa Regency. The performance of village officials plays a crucial role in ensuring effective village governance and quality public services. This research employed a quantitative approach with an explanatory research design. Data were collected using structured questionnaires with a Likert scale and analyzed through simple linear regression. The research population consisted of all village officials in the selected villages, and a census sampling technique was applied. The results indicate that the leadership style of the village head has a positive and significant effect on the performance of village officials. Leadership characterized by clear direction, effective communication, and supportive supervision contributes to improved work quality, responsibility, and teamwork among village officials. These findings highlight the strategic role of village head leadership in enhancing the performance of village administration. Strengthening leadership capacity at the village level is therefore essential to improve governance effectiveness.